Impact of Technology from Learning Environment to Organizational Practices - Alkhabra, Saleh; Abdullah, Natrah (International Journal of Social Sciences and Management, 2016)
Technology has been widely adopted in the learning environment to replace conventional face-to-face learning system. The attractiveness of technology into learning was supported by its convenient, versatile, interactive and effectiveness in delivering learning even at remote environment. Flexibility afforded by online learning environment allows its users to interactively transfer knowledge and skills to other users. These learning features promoted the popularity technology integration into learning environment which has been central to converting the abundance information available online and raw data available in organizations into database to improve business activities. In this review, issues arising from knowledge creation and management have been discussed as well as the relevancy of the interactive learning environment afforded by technology. Technology-based learning was found to have become integral part of life and has promoted learning isolated environment. Knowledge creation and management were found to be more effective when they are integrated to resolve organization problems. This paper supported that both knowledge creation and knowledge management are crucial components to create a strategic business advantage. Int. J. Soc. Sci. Manage. Vol-3, issue-2: 108-114